Morphogenic and structural characteristics of Panicum cultivars during the establishment period in the Brazilian Northeast - Costa, Ana Beatriz Graciano da; Difante, Gelson dos Santos; Gurgel, Antonio Leandro Chaves; Veras, Emmanuel Lievio de Lima; Rodrigues, Jéssica Gomes; Pereira, Marislayne de Gusmão; Santos, Anna Yanka de Oliveira; Emerenciano Neto, João Virgínio; Montagner, Denise Baptaglin (Acta Scientiarum. Animal Sciences, 2020)
This study aimed to evaluate the morphogenic and structural characteristics of six Panicum maximum cultivars during the establishment period. A completely randomized block design with four replicates and six treatments (Tamani, Mombaça, Massai, Tanzania, Aruana and Zuri cultivars) was used. Morphogenic (leaf appearance rate, leaf elongation rate e stem elongation rate), structural (final leaf length, tiller population density e number of leaves per tiller) and productive (forage mass, leaf blade mass, stem mass, senescent material mass and leaf:stem ratio) characteristics were evaluated. There was no difference (p > 0.05) between the cultivars in terms of the number of live leaves per tiller (2.95 leaves/tiller). Mombaça cultivar had (p < 0.05) higher canopy height (50.64 cm) compared with other cultivars. The highest (p < 0.05) tiller population density was observed in Tamani (235.90 tillers m-2) and Massai (201.60 tillers m-2) cultivars. Leaf lifespan (54.18 days), phyllochron (17.40 days/leaf) and leaf senescence rate (0.87 cm tiller day-1) were not different (p > 0.05) between cultivars. However, leaf appearance rate was higher (p < 0.05) in Tanzania (0.07 leaves tiller day-1) than in Aruana cultivar (0.05 leaves tiller day-1). Leaf blade mass was higher (p < 0.05) in Mombaça cultivar (1518.31 kg DM ha-1), whereas Massai showed higher (p < 0.05) leaf:stem ratio (9.25). Panicum cultivars Tamani, Tanzania and Massai establishment after 75 days, while the other cultivars establish at 105 days of sowing in the Brazilian Northeast.